2021
DOI: 10.1177/0193945920988840
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Insomnia Symptoms With Cognition in Persons With Heart Failure

Abstract: Although cognitive impairment is common among persons with heart failure and negatively impacts self-care, hospitalization, and mortality, the associations between cognitive impairment and insomnia symptoms are not clearly understood. The purpose of this study was to explore these associations and examine if they are maintained after adjusting for relevant sociodemographic, clinical, and lifestyle factors. Guided by the Neurocognitive model of insomnia and sleep and the self-care conceptual model, a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The articles were collected from studies conducted in various countries. These countries include the United States (7) (Gary et al, 2019 ; Gharzeddine et al, 2021 ; Kuhn et al, 2022 ; Lee et al, 2019 ; Pandey et al, 2019 ; Pastva et al, 2021 ; Redwine et al, 2020 ), Netherlands (1) (Kuipers et al, 2022 ), Sweden (1) (Holm et al, 2020 ), Italy (1) (Vellone et al, 2020 ), Portugal (2) (Fino et al, 2020 ; Rigueira et al, 2021 ), Australia (2) (Aili et al, 2022 ; Huynh et al, 2021 ), Japan (4) (Saito et al, 2020 ; Seo et al, 2024 ; Sugie et al, 2018 ; Yamamoto et al, 2022 ), South Korea (2) (Kim et al, 2019 ; Seo et al, 2023 ), and China (1) (Miao et al, 2023 ). Seven articles were in inpatient settings (Holm et al, 2020 ; Huynh et al, 2021 ; Miao et al, 2023 ; Pandey et al, 2019 ; Pastva et al, 2021 ; Rigueira et al, 2021 ; Seo et al, 2024 ) and the rest were in outpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“…The articles were collected from studies conducted in various countries. These countries include the United States (7) (Gary et al, 2019 ; Gharzeddine et al, 2021 ; Kuhn et al, 2022 ; Lee et al, 2019 ; Pandey et al, 2019 ; Pastva et al, 2021 ; Redwine et al, 2020 ), Netherlands (1) (Kuipers et al, 2022 ), Sweden (1) (Holm et al, 2020 ), Italy (1) (Vellone et al, 2020 ), Portugal (2) (Fino et al, 2020 ; Rigueira et al, 2021 ), Australia (2) (Aili et al, 2022 ; Huynh et al, 2021 ), Japan (4) (Saito et al, 2020 ; Seo et al, 2024 ; Sugie et al, 2018 ; Yamamoto et al, 2022 ), South Korea (2) (Kim et al, 2019 ; Seo et al, 2023 ), and China (1) (Miao et al, 2023 ). Seven articles were in inpatient settings (Holm et al, 2020 ; Huynh et al, 2021 ; Miao et al, 2023 ; Pandey et al, 2019 ; Pastva et al, 2021 ; Rigueira et al, 2021 ; Seo et al, 2024 ) and the rest were in outpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis was part of a larger secondary data analysis of the health and retirement study (HRS) wave 2016 (Health and retirement study, 2019b). Details of the design and methods of the HRS study and the larger analysis were reported previously (Gharzeddine, 2020; Gharzeddine et al, 2021) and are summarized here for clarity.…”
Section: Methodsmentioning
confidence: 99%
“…Poor sleep quality is common among patients with HF and might be an independent predictor of cardiac events. According to previous studies, potential factors, including sociodemographic, illness‐related and psychological factors, may contribute to sleep disorders in HF (Gharzeddine et al, 2021). Wang et al (2010) showed that gender, perceived health, depressed mood and the number of complications are related to poor sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Chimluang et al (2017) reported that anxiety, depression, marital status, dyspnoea, dysfunctional beliefs and attitudes about sleep are related to poor sleep quality, rather than age, gender and sleep hygiene. In addition, many studies attributed sleep disturbance to the symptoms of poor control HF, such as pain and volume overload (Conley et al, 2019; Gharzeddine et al, 2021). However, previous findings are inconsistent.…”
Section: Introductionmentioning
confidence: 99%